Mathematical Concepts and Cultural Values in Sonaf Tamkesi: Ethnomathematics Study in a Traditional Village on Timor Island - Funan, Fedelia; Son , Aloisius Loka; Siahaan, Meiva Marthaulina Lestari (S&Co Publishing, 2024)
Mathematics is a universal science, and it is crucial for everyone to master it, both in terms of its applications and its cognitive patterns. The purpose of this research is to explore the concepts of mathematics and cultural values found in the artifacts of Sonaf Tamkesi Manufui. The study was conducted in the traditional village of Tamkesi, south Biboki District, North Central Timor Regency, in July 2023. The subjects of this study were three community leaders. The type of data collected for this research was primary data obtained through documentation and interviews between the researcher and the respondents. Data analysis was conducted through stages of domain analysis, taxonomy, componential analysis, and cultural themes. The research findings indicate that there are concepts of plane geometry in the artifacts such as trapeziums, rectangles, squares, rhombuses, triangles, circles, cylinders, hexagons, and cubes. Meanwhile, the cultural values of the artifacts in Sonaf Tamkesi are the roof symbolizes harmony, the door symbolizes greatness and respect for ancestors, the pillars symbolize vertical relations with ancestors, the betel-nut container symbolizes service, the clay pot symbolizes a gift from ancestors to the living, the hearth symbolizes balance, and harmony in achieving goals.